Fish Bones as Calcium Source: Bioavailability of Micro and Nano Particles - Benjamín Torres; Alvaro Pérez; Paula García; Paula Jiménez; Karen Abrigo; Pedro Valencia; Cristian Ramírez; Marlene Pinto; Sergio Almonacid; Manuel Ruz (Foods, 2024)
The amount of by-products/waste in the fish industry is roughly 50%. Fish bones could be used to produce nanoparticles, which may have potential use in the food industry as a novel calcium source and at the same time, contribute to reduce waste production. The objective of this study was to evaluate the bioavailability of nano-size salmon fish bone particles compared to micro-size salmon fish bone particles, and calcium carbonate. The study was carried out in 21–28-day-old C57BL/6 male mice fed for 21 days with the experimental diets. The groups were as follows: CaCO3 0.5% Ca (CN 0.5); CaCO3 1.0% Ca (CN 1.0); salmon fish bone (SFB) microparticles 0.5% Ca (MP 0.5); SFB microparticles 1.0% Ca (MP 1.0); SFB nanoparticles 0.5% Ca (NP 0.5); and SFB nanoparticles 1.0% Ca (NP 1.0). Calcium bioavailability, defined as the percent calcium in femur showed an increasing trend from CN 0.5 to NP 1.0 group. According to ANCOVA, the greatest Ca content was observed in the NP 1.0 group compared with all groups but NP 0.5. In conclusion, in a murine model, salmon fish bone nanoparticles present higher calcium bioavailability than salmon fish bone microparticles, and both, in turn, have better bioavailability than calcium carbonate.